ANALISIS PENGARUH DANA PIHAK KETIGA, SUKU BUNGA DAN INFLASI TERHADAP PENYALURAN KREDIT - Riyantowo, Dianing Saleha; Arifin, Zainal; Sari, Novi Primita (Program Studi Ekonomi Pembangunan, 2021)
The purpose of this research is to find out whether there is an influence on the variables of third party funds, interest rates, and inflation on credit distribution provided by commercial banks and to strengthen the results of previous research. The data sources for this research were obtained from the official website of the Central Statistics Agency, Bank Indonesia, and the Indonesian Banking Statistics or the Financial Services Authority. The analytical technique used is descriptive quantitative technique, it is to explain the influence between the variable lending funds and the variable third party funds, interest rates, inflation. The results of the separate test (t test) obtained The results have a significant positive effect on the third party fund variable and on the interest rate variable, while the inflation variable has a negative and insignificant effect on lending, meaning that if the inflation rate is high, lending will decrease.